Optimization of sodium starch glycolate and maltodextrin in chlorpheniramine maleate Fast Disintegrating Tablet (FDT) by factorial design - Sutristio, Kezia Livianthi Kirana Budhi; Lestari, Agatha Budi Susiana (Faculty of Pharmacy, Universitas Pancasila, 2024)
Chlorpheniramine maleate (CTM) is an antihistamine that is widely available on the market in tablet form. It needs to be formulated in the form of Fast Disintegrating Tablets (FDT) to produce a faster therapeutic effect to treat allergy symptoms, which are often irritating. The FDT contains a super disintegrant to regulate the disintegration speed of tablet and a binder to provide the ability to bind between powders. This research was conducted to obtain the effect of Sodium Starch Glycolate (SSG) as a super disintegrant and maltodextrin as a binder, and their interaction in the chlorpheniramine maleate tablet formulation. This research was categorized as true experimental designs with FDT quality parameters such as organoleptic, hardness, friability, disintegration time, wetting time, water absorption ratio, and content uniformity. The optimization method used is factorial design. Data analysis was performed using Analysis of Variance (ANOVA). Based on the data, it conclude that Sodium Starch glycolate (SSG) affects increasing hardness, increasing friability, extending disintegration time, extending wetting time, and reducing the water absorption ratio. Maltodextrin, has the effect of increasing hardness, reducing friability, extending disintegration time, extending wetting time, and reducing the water absorption ratio. The interaction of SSG and maltodextrin has the effect of reducing hardness, increasing friability, shortening disintegration time, shortening wetting time, and increasing the water absorption ratio.